PERBEDAAN NILAI TOTAL LUNG CAPACITY, PEAK EXPIRATORY FLOW DAN EXPIRATORY RESERVE VOLUME ANTAR CABANG OLAHRAGA PADA ATLET USIA 6-12 TAHUN - Radyoko Heru Rahbanu; Yuswo Supatmo; Endang Kumaidah (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2016)
Background: The development of a person's lungs are the most rapidly while still a child. Activity plays an important role in lung development. Research shows that exercise a positive impact on the development of lung and cardiovascular function. Each type of sport has a different energy system depends on the type of trainingObjective: To prove the difference in value of TLC, PEF and ERV among sports in athletes aged 6-12 years.Methods: This study used a descriptive analytic study is not paired with the cross-sectional design. Samples were 20 male athletes 6-12 years in the sport Volleyball, Soccer, Swimming and Taekwondo. Data retrieval characteristics such as age, height, weight, chest circumference and BMI. TLC values, PEF and ERV is measured by using a spirometer Spirolab II. Statistical test using Kruskal Wallis test.Results: The mean value of the group TLC Volleyball athletes was 2.21 L, athletes Football is 3.4 L, athletes Pool was 3.68 L and Taekwondo athletes was 3.19 L. The mean value of PEF group of athletes Volleyball is 4, 45 L / min, athletes Football is 3.8 L / min, athletes Pool was 4.44 L / min and Taekwondo athletes was 4.09 L / min. The mean value of ERV group of athletes was 0.75 L Volleyball, athletes Football is 0.53 L, 0.54 L Swimming athletes and athletes Taekwondo 0.49 L.Conclusion: In this study, there were significant differences between the average value of TLC sport athletes 6-12 years of age. Meanwhile, there was no significant difference in the average value of PEF and ERV sports athletes aged between 6-12 years.